(untitled) (Cadernos de Sociomuseologia, 2012)
Due to various reasons museum employees from the Baltic States rarely use the chance to study museology abroad. Therefore the State Authority on Museums of Latvia in collaboration with ICOM-Latvia decided to ―deliver‖ this knowledge, by inviting internationally acknowledged lectors from different countries to widen the scope of takers of this opportunity. Estonian and Lithuanian colleagues are also joining in the project, which is included in the cooperation programme of the Ministries of Culture of the Baltic States.